Analysis of Factors Influencing the Incidence of Labor Complications in the Era of Health Digitalization in Malang Regency - Raden Maria Veronika Widiatrilupi; Retno Dewi Prisusanti; Anik Purwati (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
The incidence of labor complications is one of the main challenges in maternal health. With the rapid development of digital technology, many health facilities have begun to integrate digital systems into health services. According to data from the Ministry of Health, the number of labor complications is still high, especially in areas with limited access to quality health facilities. Various factors, such as maternal age, nutritional status, education, and access to health services, contribute to the risk of complications that can endanger the health of mothers and babies.Objective: This study aims to analyze the factors that influence the incidence of childbirth complications in the era of health digitalization.Method: This type of research uses a quantitative approach with the Cross-Sectional Survey method. The population in this study were mothers who gave birth in health facilities in Malang Regency. The research sample was taken using a purposive sampling technique, which included pregnant women with a history of childbirth complications and the use of digital health services in the period 2023-2024. Sample: A total of 50 pregnant women were taken. The results of this study indicate a significant relationship between sociodemographic factors and the incidence of childbirth complications in Malang Regency, with a p value = 0.030 (p <0.05). This finding is in line with various previous studies that identified education, maternal age, age of marriage, and parity as important determinants of the incidence of childbirth complications. These findings confirm that although digital technology is increasingly developing in health services, fundamental factors such as maternal sociodemographic characteristics remain important determinants of the incidence of childbirth complications.